Prediction and experimental characterization of the molecular architecture of FRP and ATRP synthesized polyacrylate networks - Gonçalves, Miguel A.D. (2009)
Prediction and Experimental Characterization of the Molecular Architecture of FRP and ATRP Synthesized Polyacrylate Networks